Collimo, un verbo fantasma - Domínguez Domínguez, Juan Francisco (Cuadernos de Filología Clásica. Estudios Latinos, 2007)
In this article we maintain that collimo is a «phantom-verb» that ought to be eliminated not only from future Latin dictionaries but also from the texts of Apuleius, Cicero and Aulus Gellius.